Political Communication Of West Java PDP PDIP In Winning The 2024 Presidential Election: Post-Jokowi Effects - Maduratmi, Rini; Solihah, Ratnia; Witianti, Siti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
In the last centuries, the development of democracy cannot be separated from the role of political communication. In West Java, political communication of DPD (Regional Representative Council) PDIP (Partai Demokrasi Indonesia Perjuangan) in winning the 2024 election requires structured and strategic planning in the contemporary political context. Effective politics can mobilize support, shape public opinion, and influence election outcomes. In the 2024 election, PDIP got a drastic drop in votes, namely being in fifth place with the badly loss of Ganjar-Mahfud in this province. This study aims to analyze the political communication of the West Java DPD PDIP in winning the 2024 election with the post-Jokowi-Effect. This qualitative study used a descriptive analysis. The results of the study showed that the political communication of the West Java DPD PDIP in winning the 2024 election was optimal in terms of communication elements such as the communicator, message content, media used, target audience, and final effect. The decline in PDIP votes in this province and the bad loss of Ganjar-Mahfud were caused by other factors, not by the political communication, namely the strong Jokowi-Effect in the use of "Jokowi Elements", the elite power factor of former PDIP and the performance of regional heads from PDIP. They all cause the poor work of this political party machine.Keywords: Political Communication, elections, political parties